Penerapan Pengolahan Kelapa Menjadi Minyak Murni (VCO) Menggunakan Teknologi Pemanas Buatan - Khusna Dwijayanti; Eko Darmawanto; Khotibul Umam (Universitas Islam Nahdlatul Ulama Jepara, 2018)
This community service activities aim to: 1) increase the creativity and innovation of members to make processed coconut products; 2) increase partner understanding of Virgin Coconut Oil (VCO) processing that is able to provide economic and health impacts; 3) increase the ability of members in designing the packaging for coconut products. This community service implementation method is an empowerment model for partners, namely PKK RT 02 RW 07 Demaan group, Jepara sub-district, with the following steps: 1) Preparation Stage; 2) Assessment Phase; 3) Stage of Alternative Planning Programs or Activities; 4) Formulation Phase of the Action Plan; 5) Stage of Implementation (Implementation) of Programs or Activities; 6) Evaluation Phase. The results obtained from this activity include: 1) Partners have creativity in running the PKK group program; 2) partners have the ability to process VC) as a means of improving the quality of the PKK program; 3) Partners in the process of producing VCO; 4) Partners understand the benefits of VCO for economic and health;